Residing Tradition of Muslim Community in Java Northern Coastal - Atiek Suprapti; Dhanoe Iswanto (Journal of Architectural Design and Urbanism, 2018)
The development of globalization has been encouraged social changing of the city. The  less social  behaviour occured in the daily of urban  community and has became a preferred  life style. This situation will be a seriouse threat for  the urban social life. A good city should be able to create many places for its people, that could make people feel comford and feel like home to live inside. A place expresses its local culture has potential to be a local identity. Locatity is  an imporant point that is needed by a nation to attrach  roles in globalization era.   The characteristic of muslim city is a place to muslim community live in that do the Idlamic shariah well. Since in the 11’th century the region of north coast of Java has been known as an entrance  gate of Islam teaching in Indonesia. The region of Demak and Kudus are the old city which are saving many artefact and tradition of living of muslim community. Kauman is an important place related to this case.  The purpose of this paper is to describe the phenomena of Muslim residence  present in Demak and Kudus, using descriptive qualitative methods. The result  is that the existence of Muslim residence in this region occured because  of the  strong support of coastal economic. There is a considerable difference between the Muslim residence  in Demak and in Kudus. The Muslim residence in Demak develops with the character of hierarchical, dependent society; while in Kudus develops an egalitarian and independent character of residence. In Kudus known the social kinship of  'Gusjigang', while in Demak emerged the Kasepuhan & Notobratan kinship which was the heir of Sunan Kalijaga. The characteristic of the two Muslim cities on the north coast of Java shows the uniqueness of Muslim cities that are not found in other areas.